Social epistemology in information studies: a consolidation - Martínez-Ávila, Daniel; Zandonade, Tarcísio (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2020)
The present paper aims to provide new details and information on the intellectual context in which social epistemology was born, including aspects such as its theoretical influences, intellectual contexts, and main characteristics. As methodology it presents an analysis of the writings on social epistemology by Jesse Shera and Margaret Egan selected from different and sometimes rare sources and collection. After an the analysis, the paper addresses the relationship between the historical social epistemology proposed by Margaret Egan and Jesse Shera as a discipline to investigate the foundations of librarianship and the contemporary social epistemology proposed by Steve Fuller as a program of a “naturalistic approach to the normative questions surrounding the organization of knowledge processes and products.” Both these proposals are outlined as an interdisciplinary project that is based on both philosophical epistemology and the scientific sociology of knowledge. Keywords: Social epistemology. Jesse Shera; Margaret Egan. Sociology of knowledge. Link: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/9839/6281